2017
DOI: 10.3899/jrheum.161040
|View full text |Cite
|
Sign up to set email alerts
|

Pomalidomide in Patients with Interstitial Lung Disease due to Systemic Sclerosis: A Phase II, Multicenter, Randomized, Double-blind, Placebo-controlled, Parallel-group Study

Abstract: Because of recruitment challenges, subject enrollment was discontinued early. In an interim analysis, the study did not meet its Week 52 primary endpoints. Therefore, a decision was made to terminate all study phases. POM was generally well tolerated, with an adverse event profile consistent with the known safety and tolerability profile of POM in other diseases. Study results were neither positive nor negative because too few subjects were enrolled to make meaningful conclusions. Clinical Trials number: NCT01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 10 publications
1
18
0
2
Order By: Relevance
“…In addition, the higher than expected numbers of skin fibrosis regressors18 and stable patients reduced the sensitivity of RISE-SSc to detect a significant change of mRSS. This is consistent with previous trials, in which mRSS improvements were observed in the majority of patients receiving placebo 32 33. Other possible explanations include the very large variation in mRSS scores during the study.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the higher than expected numbers of skin fibrosis regressors18 and stable patients reduced the sensitivity of RISE-SSc to detect a significant change of mRSS. This is consistent with previous trials, in which mRSS improvements were observed in the majority of patients receiving placebo 32 33. Other possible explanations include the very large variation in mRSS scores during the study.…”
Section: Discussionsupporting
confidence: 91%
“…Several other medications (imatinib, bosentan, pomalidomide, abituzumab, tadalafil, abatacept, belimumab, brentuximab, lenabasum, and riociguat) have been examined with varying results and without strong evidence to date to support clinical utility in SSc-ILD [126][127][128][129][130][131][132][133][134][135][136] (►Tables 1 and 2).…”
Section: Rituximabmentioning
confidence: 99%
“…Pirfenidone has already been evaluated in a small phase II study (LOTUSS) [135] and the SLS III trial comparing MMF combined with pirfenidone treatment and MMF treatment alone is ongoing [136] [https://clinicaltrials.gov/ct2/show/NCT03221257] A large phase III trial investigating the safety and efficacy of nintedanib in SSc-associated lung fibrosis is ongoing [137,138, https://clinicaltrials.gov/ct2/show/NCT02597933]. However, trials of lung fibrosis in SSc are challenging and some studies have failed to recruit enough patients [139] or have had unequivocally negative results [140,141].…”
Section: [H2] Treatment Approaches For Lung Fibrosismentioning
confidence: 99%